PENINGKATAN KINERJA GURU MELALUI SUPERVISI PENGAWAS SATUAN PENDIDIKAN DAN KEPEMIMPINAN KEPALA SEKOLAH (STUDI KASUS PADA SMA MA’ARIF NU 5 PURBOLINGGO KABUPATEN LAMPUNG TIMUR) - Mustofa, Dwi Rohmadi; Marzuki, Ide Lia; Mustofa, Ihsan (STIT Pringsewu, 2017)
The purpose of this study was to determine; (1) positive influence and significant correlation between the regulatory supervision of the educational unit on teacher performance of the SMA Maarif NU 5 Purbolinggo, East Lampung regency; (2) positive influence and significant correlation between school leadership on teacher performance; (3) positive and significant influence between the regulatory supervision of the education unit and school leadership together on teacher performance.Population or census, the permanent teachers in high school Maarif NU 5 Purbolinggo totaling 36 people. Primary data was collected by a questionnaire instrument. Data were analyzed qualitatively and quantitatively with the correlation formula, linear regression and multiple linear regression.The results showed; (1) a significant difference supervisors supervising teacher education unit on the performance of the SMA Maarif NU 5 Purbolinggo, East Lampung regency; (2) there is a significant impact of school leadership on teacher performance; (3) there is a significant influence supervision unit superintendent of education and school leadership together on teacher performance.